Chromosome-level genome assembly of Ceroplastes pseudoceriferus Green, 1935 (Hemiptera: Coccidae) - Yaoguang Qin; Zhennan Wang; Jiangni Li (Scientific Data)
Abstract Soft scales (Hemiptera: Coccidae) are significant polyphagous pests and majority of which are invasive species. The 364.14 Mb chromosome-level genome of Ceroplastes pseudoceriferus was assembled in this work, with a contig N50 length of 6.16 Mb and scafold N50 length of 21.24 Mb. Approximately 99.89% of assembled sequences were anchored into 18 chromosomes with the assistance of Hi-C reads. Furthermore, approximately 53.98% of the genome was composed of repetitive elements. In total, 10,475 protein-coding genes were predicted, of which 9503 (90.72%) genes were functionally annotated. The BUSCO analysis demonstrated the completeness of the genome annotation is 92.54%. This genome represents first high-quality chromosome level assembly of Coccidae, thereby advancing our knowledge of Coccidae insects and developing effective management strategies that protect crops, forests, and natural ecosystems.